A talent for murder ebook A novel. - Swanson, Peter (2024)
A newlywed librarian begins to suspect the man she married might be a murderer—in this spectacularly twisty and deviously clever novel by Peter Swanson, New York Times bestselling author of The Kind Worth Killing and Eight Perfect Murders. Martha Ratliff conceded long ago that she'd likely spend her life alone. She was fine with it, happy with her solo existence, stimulated by her work as a librarian in Maine. But then she met Alan, a charming and sweet-natured salesman whose job took him on the road for half the year. When he asked her to marry him, she said yes, even though he still felt a little bit like a stranger. A year in and the marriage was good, except for that strange blood streak on the back of one of his shirts he'd worn to a conference in Denver. Her curiosity turning to suspicion, Martha investigates the cities Alan visited over the past year and uncovers a disturbing pattern—five unsolved cases of murdered women. Is she married to a serial killer? Or could it merely be a coincidence? Unsure what to think, Martha contacts an old friend from graduate school for advice. Lily Kintner once helped Martha out of a jam with an abusive boyfriend and may have some insight. Intrigued, Lily offers to meet Alan to find out what kind of man he really is . . .but what Lily uncovers is more perplexing and wicked than they ever could have expected.